Soluble tumor necrosis factor alpha promotes retinal ganglion cell death in glaucoma via calcium-permeable ampa receptor activation - Cueva Vargas, Jorge L. (2015)
Loss of vision in glaucoma results from the selective death of retinal ganglion cells (RGCs). Tumor necrosis factorα (TNFα) signaling has been linked to RGC damage, however, the mechanism by which TNFα promotes neuronal death remains poorly defined. Using an in vivo rat glaucoma model, we show that TNFα is upregulated by Müller cells and microglia/macrophages soon after induction of ocular hypertension. Administration of XPro1595, a selective inhibitor of soluble TNFα, effectively protects RGC soma and axons. Using cobalt permeability assays, we further demonstrate that endogenous soluble TNFα triggers the upregulation of Ca2+-permeable AMPA receptor (CP-AMPAR) expression in RGCs of glaucomatous eyes. CP-AMPAR activation is not caused by defects in GluA2 subunit mRNA editing, but rather reflects selective downregulation of GluA2 in neurons exposed to elevated eye pressure. Intraocular administration of selective CP-AMPAR blockers promotes robust RGC survival supporting a critical role for non-NMDA glutamate receptors in neuronal death. Our study identifies glia-derived soluble TNFα as a major inducer of RGC death through activation of CP-AMPARs, thereby establishing a novel link between neuroinflammation and cell loss in glaucoma.